A new chondrichthyan fauna from the Late Jurassic of the Swiss Jura (Kimmeridgian) dominated by hybodonts, chimaeroids and guitarfishes. (4th August 2017) - Leuzinger, Léa; Cuny, Gilles; Popov, Evgeny; Billon‐Bruyat, Jean‐Paul
Abstract: The fossil record of chondrichthyans (sharks, rays and chimaeroids) principally consists of isolated teeth, spines and dermal denticles, their cartilaginous skeleton being rarely preserved. Several Late Jurassic chondrichthyan assemblages have been studied in Europe based on large bulk samples, mainly in England, France, Germany and Spain. The first study of this kind in Switzerland is based on controlled excavations in Kimmeridgian deposits related to the construction of the A16 motorway in the Swiss Jura (Porrentruy, NW Switzerland). This study is based on more than 2000 isolated chondrichthyan remains (teeth, dental plates, spines and dermal denticles) and adds to our knowledge of the chondrichthyan distribution at a regional scale in Europe. We describe and identify this new fauna, define a new species of hybodont with crushing‐type dentition ( Asteracanthus udulfensis sp. nov.) and report for the first time the carcharhiniform Corysodon cirinensis in Switzerland. By the Late Jurassic, modern neoselachian sharks had overtaken hybodonts in European marine realms, the latter being gradually confined to brackish or freshwater environments. However, while the associated fauna of the Porrentruy platform indicates marine conditions, neoselachian sharks are surprisingly rare. The chondrichthyan assemblage is largely dominated by hybodonts, guitarfishes (rays) and chimaeroids that are all known to be euryhaline. This unexpected chondrichthyan faunal composition questions the presence of fresh to brackish water in the vicinity of the platform, and the occurrence of salinity fluctuations within a general context marine. This could explain the scarcity of neoselachian sharks and the extended success of hybodonts in the Porrentruy area as late as the Late Jurassic.